Unraveling the Resistome, Virulome, and Pathogenicity of Escherichia Coli O157:H7 From Cattle Feces - Bukola Opeyemi Oluwarinde; Daniel Jesuwenu Ajose; Tesleem Olatunde Abolarinwa; Peter Kotsoana Montso; Henry Akum Njom; Collins Njie Ateba (International Journal of Microbiology, 2025)
Antimicrobial-resistant Escherichia coli, especially those belonging to the serotype O157, are increasingly linked to foodborne diseases with significant fatality rates worldwide. The food and medical industries have focused on E. coli O157:H7 due to its ability to produce toxins coupled with its low infectious dose. The aim of this study was to assess the virulome, resistome, and pathogenicity of E. coli O157:H7 using whole genome sequencing. Three previously isolated E. coli O157:H7 strains from cattle feces were subjected to whole genome sequencing. The genome sizes of all three E. coli O157:H7 strains were 5,117,276 bp, 5,039,443 bp, and 5,034,351 bp. The C + G contents were 50.22%, 50.53%, and 50.54%, while the number of contigs was 110, 43, and 42, respectively, for E. coli O157:H7 strains J32, J57, and J69. Several virulence determinants (hemorrhagic E. coli pilus (HCP), eaeA, hemolysin, etc.) were found in the genomes of these isolates. In addition, antibiotic resistance genes conferring resistance to aminoglycosides, tetracyclines, macrolides, fluoroquinolones, penams, carbapenems, cephalosporins, cephamycin, rifamycin, phenicols, monobactams, and nitroimidazole were found in the genomes. Interestingly, the genomes of these isolates also harbored determinants encoding resistance to disinfectants and antiseptics, indicating their concern in the food production and medical sectors. This highlights the public health concerns of these isolates, indicating the need for constant surveillance.